Legitimate histories - Robertson, Fiona (Clarendon, 1994)
This text provides a reading of Walter Scott's
10.1093/acprof:oso/9780198112242.001.0001
Keywords: Scott; Walter; Waverley novels; Historical fiction; English; Gothic revival (Literature); Authority in literature